Wspomaganie controllingu logistyki w obszarze zaopatrzenia towarowego w przedsiębiorstwie handlowym - Skoczylas, Krystyna (The Aid of Logistics Controlling in the Area of Supply in a Commercial Enterprise, 2007)
The paper presents the possibility of utilisation of logistics controlling in the supply area. Several examples of prognosis of sale of commodities are given. Neural network is used for forecasting.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1174, s. 454-458